International terrorism in the 1980s : a chronology of events - Edward F. Mickolus, Todd Sandler, and Jean M. Murdock. (Iowa State University Press, 1989)
Vol. 1. 1980-1983 - Vol. 2. 1984-1987. Includes bibliographical references.